Fourier Transform Infrared Spectroscopy enables rapid differentiation of fresh and frozen/thawed chicken. (February 2016) - Grunert, Tom; Stephan, Roger; Ehling-Schulz, Monika; Johler, Sophia
Abstract: Freezing and thawing affect the sensory profile and the quality of chicken meat, resulting in lower marketability. Retailers are faced with the risk of mislabeling, as fresh and frozen/thawed chicken meat are visually indistinguishable and as there is currently no fast, reproducible, and inexpensive technique for the differentiation of fresh and frozen/thawed chicken implemented in practice. Fourier Transform Infrared (FTIR) spectroscopy represents a new promising technique that determines the overall chemical composition of a sample, thus creating a metabolic spectral fingerprint that can be analyzed by various pattern recognition algorithms. In this study, we aimed to assess the performance of FTIR spectroscopy when applied to the differentiation of fresh and frozen/thawed chicken meat. To this end, we compared the FTIR spectra of chicken stored at 4 °C to those of chicken that was frozen and stored at −20 °C for 2, 5, 15, 30, 60, 70, and 85 days. Hierarchical cluster analysis of FTIR spectra allowed to distinguish fresh samples from samples that have been frozen for longer periods. Samples of frozen storage of 15, 30, 75 and 85 days could be clearly identified as such. Further, the potential of combining FTIR spectroscopy with artificial neuronal network (ANN) analysis to enable identification of even shortly frozen products was determined. Twenty out of 21 samples were correctly classified in either fresh or frozen/thawed chicken meat based on the internal validation including frozen/thawed chicken meat samples derived from day 2 and 5. In conclusion, we provide proof of principle that FTIR spectroscopy enables rapid and reliable discrimination of fresh from frozen/thawed chicken meat. Due to its high–throughput capacity, it could represent a promising tool in routine inspections differentiating fresh from previously frozen meat products such as beef, pork, lamb and turkey. Highlights: FTIR spectroscopy can be used to differentiate fresh and frozen/thawed chicken. Supervised learning algorithms distinguish FTIR spectra of fresh and frozen meat. FTIR spectra differed in the amide I region (1660–1628 cm −1 ).